Guidance for Autistic Children in Improving Social Interaction Ability in Sekolah Khusus Taruna Al-Qur’an - Zahra, Fathimatuz; Bahiroh, Siti (Universitas Muhammadiyah Yogyakarta, 2022)
Autism is a developmental disorder that usually occurs in children. This disorder is characterized as an inability to interact with others in the form of a language disorder indicated by delayed language acquisition. Meanwhile, as humans, we are social creatures who definitely need help from others. Social interaction is key for a human being to adapt to his environment. Without interaction, there is no such thing as communal life. This study aims to determine the model of guidance for autistic children used in the Sekolah Khusus Taruna Al-Qur'an to improve students' social interaction skills. This study uses descriptive qualitative research methods. Data was collected by means of observation, in-depth interviews, and documentation. The result of this research is that the Sekolah Khusus Taruna Al-Qur'an provides guidance in the form of speech therapy which is handled by competent therapists in their fields, and also guidance in the classroom using structured learning methods with a model of 1 or 2 students 1 teacher. Furthermore, after being given guidance, students show good changes, namely starting to focus on eye gaze and also the emergence of an understanding of how to convey desires or feelings appropriately. Obstacles in this guidance process are the variety of parenting styles of each student, unmaintained eating patterns, and limited infrastructure.